Cannabidiol for Treatment of Childhood Epilepsy–A Cross-Sectional Survey - Klotz, Kerstin A.; Schulze-Bonhage, Andreas; San Antonio-Arce, Victoria; Jacobs, Julia (Frontiers in Neurology, 2018)
BACKGROUND The interest in cannabidiol (CBD) for treatment of epilepsy has been increasing over the last years. However, practitioner´s attitudes concerning the use of CBD for epilepsy treatment appears to be divided and data about its clinical use in daily practice are not available. OBJECTIVE To improve the knowledge about the current use of CBD amongst European practitioners treating children and adolescents for epilepsy. METHODS Cross-sectional survey using an open-access online questionnaire for physicians treating children or adolescents for epilepsy within eight European countries from December 2017 to March 2018. RESULTS One-hundred fifty-five physicians participated in the survey. CBD is increasingly used by 45% (69/155) of participants. The median (range) number of treated patients per participant is 3 (1-35). Only 48% of the participants prescribing CBD are exclusively using purified CBD to treat children and adolescents with epilepsy, the remainder also applies preparations containing delta9-tetrahydrocannabinol (THC). Reported daily CBD doses range from < 10 to 50 mg/kg body weight. Management of CBD therapy in regard of monitoring side effects and adjusting concomitant therapy differs widely amongst participants. Their primary objective for commencing CBD is improving patient’s quality of life. Participants frequently receive inquiries about CBD treatment but only 40% may actively suggest CBD as a treatment option. Of the 85 participants currently not using CBD for epilepsy treatment, 70% would consider using CBD if available in their country of practice or given the opportunity to become familiar with this treatment option. CONCLUSIONS CBD is increasingly used by participating physicians but individual experience remains limited. There are very diverse opinions about the use of CBD to treat epilepsy in children and adolescents and widely differing views on how to manage the CBD treatment.